Toxicological Effects of Perfluoroalkyl and Polyfluoroalkyl Substances - DeWitt, Jamie C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Humana, 2015)
This book serves as a timely and comprehensive overview of the latest science for perfluoroalkyl and polyfluoroalkyl substances (PFASs), covering the development of methods for assessing PFASs in biological fluids and tissues as well as the current knowledge regarding their toxicity to vertebrate organisms. This book includes chapters on human and wildlife exposure/body burdens, reviews of metabolism and toxicological effects by organ system/developmental stage, and aspects of PFAS toxicity that are driving PFAS research and regulatory oversight. Toxicological Effects of Perfluoroalkyl and Polyfluoroalkyl Substances provides critical assessments of the most controversial topics surrounding toxicological evaluation of PFASs to give readers an expert perspective on the issues. Emphasis is placed on the integration of modes and mechanisms of action with functional endpoints that are relevant to human and wildlife health. This book will be a useful resource for toxicologists, environmental chemists, risk assessors, and researchers with an interest in the class of compounds known as perfluoroalkyl and polyfluoroalkyl substances.
Perfluorinated compounds: An overview -- Analysis of PFASs in biological tissues and fluids -- PFASs in the general population -- PFAS Biomonitoring in Higher Exposed Populations -- Perfluorinated Alkyl Acids in Wildlife -- Metabolism and Pharmacokinetics -- Metabolic EffectsPFAS -- Developmental Toxicity -- Neurotoxicity -- Immunotoxicity of Perfluoroalkylated Compounds -- Effects of PFOA on Endocrine-related Systems -- Carcinogenicity of Perfluoroalkyl Compounds -- Epidemiological Findings -- Dosimetric Anchoring of Toxicological Studies -- Human Health Risk Assessment of Perfluoroalkyl Acids -- Systematic Review, An Illustration of Increased Transparency in a Framework for Evaluating Immunotoxicity Associated with PFOA and PFOS Exposure -- Toxicology data for alternative “short-chain” fluorinated substances -- Conclusions and recommendations.  .
Keywords: Pharmacology; Environmental health; Ecotoxicology; Pharmacology/Toxicology.; Environmental Health; Ecotoxicology